Reorientasi Gerakan Feminisme Islam; Sebuah Upaya Membangun Kesetaraan Perempuan - WARITS, ABD (FIKROTUNA: Jurnal Pendidikan dan Manajemen Islam, 2016)
In the history of women's life, the woman has never cracked from the wild cry of helplessness. Woman always become victim of men’s egoism, marginalized, hurt, unfettered, fooled and never appreciated the presence and role. This situation troubles many intellectual Muslims who have perspective that Islam teaches equality, equality for all human beings in the world. The difference in skin color, race, tribe and nation, as well as gender does not cause them to get the status of the different rights and obligations. The potential and the right to life of every human being and the obligation to serve the Lord Almighty is the same. Indeed, all human beings, as caliph in the world, have the same obligation, namely to prosperity of life in the world. No one is allowed to act arbitrarily, destroying, or hurt among others. They are required to live side by side, united, and harmonious, help each other and respect each other. However, that "demand" never becomes a reality. The differences among human identities become a barrier and the cause of divisions. For them, those who are outside environment, different identities are "others" who rightly do not need them "know". The difference of identity has become a reason to allow "hurt" each other. Several intellectual Muslims who recognize the wrong (discrimination against women), and then they attempt to formulate a movement for women's liberation. All the efforts have been done on the basis of awareness that arbitrary action by any person can never be justified. They also realize, that the backwardness of women are "stumbling block" that will lead to the resignation of a civilization. However, this struggle found a lot of challenges; including the consideration of "insubordination" to conquer the power of men, despite it had done by using many strategies. Starting from the writing of scientific book and countless fiction themed women has been published in order to give awareness of equality between men and women. This paper seeks to reexamine the process of the empowerment struggle to give a brand new concept, so that the struggle of women empowerment is not as insubordination and curiosity process in an attempt to conquer the male. Through approach of literature review and observations on the relationship between men and women, the writer finally concluded that the movement of Islamic feminism is not a movement to seize the power of men, but an attempt to liberate women from oppression so that they get the rights of their social role, giving freedom for women to pursue a career as wide as possible like a man, without forgetting a main duty as a mother: to conceive, give birth and breastfeed their children.